Depression and anxiety among people living with HIV in a coastal city of Karnataka - R., Kavya; Badiger, Sanjeev (International Journal Of Community Medicine And Public Health, 2018)
Background: Living with HIV/AIDS not only hampers physical health but also mental and social well-being. The aim of this study was to assess the proportion of depression and anxiety among people living with HIV in the coastal city of Karnataka. Methods: A cross sectional study was conducted in a community based organization in Mangaluru. It involved 169 study participants selected by simple random sampling technique. After the informed consent, the data was collected by interviewer’s method using Beck’s depression scale and Hamilton’s anxiety scale. The data was analysed using SPSS software version 22. Results: Of the 169 participants, the most prevalent age at diagnosis of HIV infection was found to be 26-34yrs (40.8%) and 57.9% belonged to rural community. 22% of them had borderline clinical depression and 12% had mild to moderate anxiety. Depression and age at diagnosis (χ2=35.199, p=0.00); relationship status (χ2=6.241, p=0.00) showed a significant association. Conclusions: Though counselling is a part of ART services but still there is lack of follow up of cases and assessing the need of psychiatric support.